Seronegative, complicated hydatid cyst of the lung: A case report - Eva Letty Susanne Engström, M.D.; Goran Nadir Salih, M.D.; Lothar Wiese, M.D., PhD, MIH (Respiratory Medicine Case Reports, 2017)
Cystic echinococcosis (CE) is an important helminthic zoonotic disease that commonly affects the liver and lungs. Imaging methods and serology establish the diagnosis in most cases. Chest x-ray can diagnose uncomplicated pulmonary hydatid cysts, whereas superinfection and/or rupture of the hydatid cyst (complicated cysts) may change the radiographic appearance and lead to delayed diagnosis and treatment. We report the case of a patient with hemoptysis and chest pain, where computer tomography scan of the lung suggested a large, ruptured hydatid cyst. However, serological tests with indirect hemagglutination (IHA)for Echinococcus granulosus antibodies were negative, and there was massive growth of Streptococcus pneumoniae in sputum. Based on this, we concluded that the patient had a bacterial lung abscess. The diagnosis of CE was only made after surgical removal of the cyst followed by microscopy and polymerase chain reaction.